Application of Fluorescent Label in Polymer Nanofibers. (17th September 2017) - Zarybnicka, Lucie; Bacovska, Radka; Nadvornikova, Zuzana; Almonasy, Numan; Syrovy, Tomas
Abstract : The electrospinning of fluorescent probe polyamide 6 doped by 7H-benzimidazo[2, 1-a]benzo[de]isoquinolin-7-on is presented as a model processing photoluminescent nanofibers. The presence of the fluorescent probe in the fiber layers was confirmed by attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR); the surface nanofiber structure was described by high-resolution fluorescence microscope and scanning electron microscope images. The prepared nanofibers with the fluorescent label were further characterized by fluorescence spectroscopy, both in the solid phase and in the solution.